OPTIMALISASI KINERJA KEUANGAN DALAM MENINGKATKAN HARGA SAHAM PERUSAHAAN SUB SEKTOR LOGAM DAN SEJENISNYA - Juwari, Juwari; Susilowati, Dwi; Karina Asih, Janet (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine the extent of optimization of financial performance in increasing the share price of metal sub-sector companies and the like, in seeing the optimization of financial performance by analyzing financial ratios which include Current Ratio, Return on Asset, and Debt to Equity Ratio. The population in this study were seventeen companies and a sample of eleven metal sub-sector companies and the like listed on the Indonesia Stock Exchange, which were taken through criteria determined by the author. The analysis method used is multiple linear regression. Based on the results of the t test (partial) that Current Ratio has an insignificant effect on Share Price, Return on Asset has a positive and significant effect on Share Price, Debt to Equity Ratio has a negative and significant effect on Share Price in Metal and Similar Sub-Sector Companies